Comparing Micro-Evidence on Rent Sharing from Two Different Econometric Models - Sabien Dobbelaere; Jacques Mairesse (Institute of Labor Economics (IZA), 2017)
Researchers contributing to the empirical rent-sharing literature have typically resorted to estimating the responsiveness of workers' wages on firms' ability to pay in order to assess the extent to which employers share rents with their employees. This paper compares rent-sharing estimates using such a wage determination regression with estimates based on a productivity regression that relies on standard firm-level input and output data. We view these two regressions as reduced-form equations stemming from, or at least compatible with, a variety of underlying theoretical structural models. Using a large matched firm-worker panel data sample for French manufacturing, we find that the industry distributions of the rent-sharing estimates based on them are significantly different on average, even if they slightly overlap and are correlated. Precisely, if we only rely on the firm-level information, we find that the median of the relative and absolute extent of rent-sharing parameters amount roughly to 0.40 and 0.30 for the productivity regression and to 0.20 and 0.16 for the wage determination regression. When we also take advantage of the worker-level information to control for unobserved worker ability in the model of wage determination, we find that these parameters further reduce as expected and have a median value of only about 0.10.
Keywords: C23; D21; J31; J51; 330; rent sharing; wage equation; production function; matched employer-employee data